2013
DOI: 10.1007/s10694-013-0365-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Building Fire Safety Performance by Reducing Miscommunication and Misconceptions

Abstract: Abstract. Building fire safety is driven by regulations and technical building codes, at least as a minimum requirement. As fire protection engineers (FPEs) design fire safety measures based on requirements in the regulations, they are often viewed as the primary agents in ensuring the fire safety of buildings. However, their mission often starts with given building design features, such as interior spatial layout, exterior shape, site plan, and so forth, which are mostly determined by architects. The only exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Other decision criteria e.g. : building aesthetics (Park et al 2014), profit-making, code compliance etc. ; and passive fire protection options e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other decision criteria e.g. : building aesthetics (Park et al 2014), profit-making, code compliance etc. ; and passive fire protection options e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified key decision criteria and sub-criteria (NZFS 1975;Spearpoint 2008;Alvarez et al 2014 andPark et al 2014)as shown in Table 3. In future, the stakeholders may be allowed to include and rate other desires they deem necessary.…”
Section: Proposed Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance value of travel time attribute may be determined based on the computer simulation results of evacuation modeling programs. In this case, however, the user need to recognize whether the imbedded features of evacuation simulation programs for exit identification such as occupant familiarity, influence of interior design, exit signage, and visual access to the exit door and their effects on the simulation results are reasonable [16].…”
Section: Fire Technology 2015mentioning
confidence: 99%
“…They did not comprehensively take into account 'soft' characteristics such as building design features, occupant activities, and the interactions among the soft characteristics and between soft and hard characteristics. This is partly because soft characteristics have not been considered as proper subjects of prescriptive codes due to their high variability and difficulties to control by codes, despite the recognition of their significant effects on building fire safety performance [16]. However, in performance-based fire safety design scheme, both hard and soft characteristics need to be included in the performance analysis since they are also significant attributes to the building fire safety performance.…”
mentioning
confidence: 99%